Chitosan level effects on fermentation profile and chemical composition of sugarcane silage - Del Valle, Tiago Antonio; Antonio, Giovani; Zilio, Elissandra Maiara de Castro; Dias, Mauro Sérgio da Silva; Gandra, Jefferson Rodrigues; Castro, Filipe Alexandre Boscaro de; Campana, Mariana; Morais, Jozivaldo Prudêncio Gomes de (Brazilian Journal of Veterinary Research and Animal Science, 2020)
This study aimed to evaluate the effects of increasing levels of chitosan (CHI) on sugarcane fermentation profile and losses, chemical composition, and in situ degradation. Treatments were: 0, 1, 2, 4, and 8 g of CHI/kg of dry matter (DM). Twenty experimental silos (PVC tubing with diameter 28 cm and height 25 cm) were used. Sand (2 kg) was placed at the bottom of each silo to evaluate effluent losses, and silos were weighed 60 d after ensiling to calculate gas losses. Samples were collected from the center of the silo mass to evaluate silage chemical composition, in situ degradation, fermentation profile, and mold and yeast count. Data were analyzed as a completely randomized design, and the treatment effect was decomposed using polynomial regression. Chitosan linearly increased acetic acid and NH3-N concentration, while yeast and mold count, and ethanol concentration decreased. Intermediary levels of CHI (from 4.47 to 6.34 g/kg DM) showed the lower values of effluent, gas, and total losses. There was a quadratic effect of CHI on the content of non-fiber carbohydrates, neutral and acid detergent, and in situ DM degradation. The lowest fiber content was observed with levels between 7.01 and 7.47 g/kg DM, whereas the highest non-fiber carbohydrate content and in situ DM degradation were found with 6.30 and 7.17 g/kg DM of CHI, respectively. Chitosan linearly increased acetic acid and NH3-N concentration, whereas it linearly reduced ethanol concentration and count of yeast and mold. Thus, intermediary levels of CHI, between 4.47 and 7.47 g/kg of DM, decrease fermentation losses and improve the nutritional value of sugarcane silage.